“Extraordinary and Compelling” Circumstances: Revisiting the Role of Compassionate Release in the Federal Criminal Justice System in the Wake of the First Step Act - O'Carroll, Siobhan A. (2021)
Lawmakers have recently revitalized compassionate release as part of a larger effort to address mass incarceration, through the First Step Act of 2018. Previously, the Bureau of Prisons (“BOP”) served a gatekeeping role for all compassionate release petitions. Now inmates may bring their petitions directly to sentencing courts after exhausting the administrative remedies available through the BOP. This change has increased the number of inmates who benefit from compassionate release. Notably, however, this change has also led to adversarial litigation of compassionate release petitions. This Note considers the constitutional implications and policy concerns arising from the updated compassionate release mechanism. Part I of this Note traces the statutory development of compassionate release in the federal prison system. Part II examines the place of compassionate release within the federal constitutional scheme. Part III turns to the policy concerns surrounding representation by appointed counsel of compassionate release petitioners. Finally, Part IV proposes expanding the guiding definitional boundaries of compassionate release and concludes by arguing for an independent body in the executive branch to handle administrative compassionate release petitions